PENGELOMPOKAN SEKOLAH MENURUT KECAMATAN DI KABUPATEN BELU MENGGUNAKAN K-MEANS BERBASIS WEBGIS - Manek, Firgilia Claudiana (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2022)
School is an education that is formal, non-formal and in formal. Access to less information about the location of schools and the spread of schools from sub-districts in Belu Regency that have an impact on the community and education implementation parties in searching or seeing related information from these schools. To overcome this problem, a school grouping system is needed based on sub-districts using webgis-based k-means that can provide convenience in seeing the location of the school and the spread of the school. Thus to see the location and spread of schools in each subdistrict in Belu regency using the K-Means method. How the k-means works to group schools by sub-district with this webgis can be more easily displayed a map of schools in Belu regency that completes a review of the school mapping. The results of this study were successfully carried out by obtaining 3 clusters consisting of cluster 1, cluster 2 and cluster 3 with the Mean Squared Error (MSE) testing is 0.035